Intraspecific killing among Leopards (Panthera pardus) in Iran (Mammalia: Felidae) - Farhadinia, M; Alinezhad, H; Hadipour, E; Memarian, I; Ostrowski, S; Hobeali, K; Dadashi-Jourdehi, A; Johnson, P; Macdonald, D; Hunter, L (Taylor and Francis, 2018)
Intraspecific aggression is one of the most common causes of death in leopards. Here, we report four cases of intraspecific killing amongst Persian Leopards (Panthera pardus saxicolor) in Iran. A young male leopard was found on 7 June 2008 which, according to camera trap images, had been killed by an adult male over a Red Deer (Cervus elaphus) kill, with trauma to his neck in Dorfak No-Hunting Area. A young female that had been fitted with a satellite GPS collar on 6 December 2015 in Tandoureh National Park died on 29 January 2016 at a site where an Urial Sheep (Ovis orientalis) ram had been freshly killed. Necropsy results, footprints at the scene of death and camera trap footage all supported the deduction that the animal was killed by a larger female leopard at the kill site. On 13 January 2017, a young, partially eaten female leopard was found with double puncture on the side of her throat. Finally, a rehabilitated adult female fitted with a satellite GPS collar found on 19 December 2017 with a double puncture on her head with several trauma and haemorrhages on her back. These instances seem to be the first documented reports of intraspecific killing among free-ranging leopards in Asia.